Molecular Characterization of Escherichia coli Producing Extended-Spectrum ß-Lactamase and MCR-1 from Sick Pigs in a Greek Slaughterhouse - Ermioni Avgere; Christos Zafeiridis; Kassandra A. Procter; Apostolos Beloukas; Panagiota Giakkoupi (MDPI AG, 2023)
The first prospective surveillance of ESBL and colistin-resistant Escherichia coli recovered from sick pigs from a slaughterhouse in Central Greece aimed to investigate the spread of relevant genetic elements. In February 2021, 25 E. coli isolates were subjected to antimicrobial susceptibility testing using disk diffusion and broth microdilution techniques. PCR screening was conducted to identify ESBLs and mcr genes. Additional assays, encompassing mating-out procedures, molecular typing utilizing Pulsed-Field Gel Electrophoresis, multilocus sequence typing analysis, and plasmid typing, were also conducted. A 40% prevalence of ESBLs and an 80% prevalence of MCR-1 were identified, with a co-occurrence rate of 32%. The predominant ESBL identified was CTX-M-3, followed by SHV-12. Resistance to colistin, chloramphenicol, cotrimoxazol, and ciprofloxacin was detected in twenty (80%), fifteen (60%), twelve (48%), and four (16%) isolates, respectively. All blaCTX-M-3 harboring plasmids were conjugative, belonging to the incompatibility group IncI1, and approximately 50 kb in size. Those carrying blaSHV-12 were also conjugative, classified into incompatibility group IncI2, and approximately 70 kb in size. The mcr-1 genes were predominantly located on conjugative plasmids associated with the IncX4 incompatibility group. Molecular typing of the ten concurrent ESBL and MCR-1 producers revealed seven multilocus sequence types. The heterogeneous population of E. coli isolates carrying resistant genes on constant plasmids implies that the dissemination of resistance genes is likely facilitated by horizontal plasmid transfer.